Potensi Penggunaan Media Sosial Bagi UKM - Wulandari, Sari; Supratman, Nurdinintya Athari (Performa: Media Ilmiah Teknik Industri, 2018)
Social media is not only a social network that facilitates social interaction, but social media becomes an effective medium used by consumers and companies. Consumers use social media to find products information, while companies use social media to communicate with their customers. Social media becomes a powerful tool for companies to reach their customers and create sales. Social media allows SMEs to compete with large companies by increasing brand awareness of their products. Many new SMEs have emerged using social media, but the use of social media is not optimal. Its because SME lack of understanding of how social media is used in an organization. Therefore, research is conducted to investigate the potential use of social media on SMEs. Qualitative method is used as data collection method by conducting interview to 15 SMEs. Qualitative data then convert to affinity diagram. Based on the affinity diagram, it can be known how SMEs use social media. The results showed that most SMEs only use social media as promotion and sales tool. Some SMEs do not manage social media properly, such as inconsistencies in updating content of social media. A few SMEs use social media as an effective marketing tool such as profiling potential customers, measuring the impact of promotion and maintaining long-term customers relationships